John Steinbeck on the street in Seville, Spain (Seville; Spain, 2022)
John Steinbeck stands on the street in Seville. The Steinbecks visited Spain during Sevilla's Feria de Abril, (April Fair) a huge festival that usually takes place two weeks after Easter. Original in safe.